2012
DOI: 10.1039/c1sm05615h
|View full text |Cite
|
Sign up to set email alerts
|

Contact-controlled amoeboid motility induces dynamic cell trapping in 3D-microstructured surfaces

Abstract: On flat substrates, several cell types exhibit amoeboid migration, which is characterized by restless stochastic successions of pseudopod protrusions. The orientation and frequency of new membrane protrusions characterize efficient search modes, which can respond to external chemical stimuli as observed during chemotaxis in amoebae. To quantify the influence of mechanical stimuli induced by surface topography on the migration modes of the amoeboid model organism Dictyostelium discoideum, we apply high resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 39 publications
3
44
0
Order By: Relevance
“…The height and diameter of the pillars is the same (8 µm) and comparable to the typical size of a D. discoideum cell, which varies between 8-15 µm 40 . This ratio between pillar height and cell size is sufficient to keep the motion of starved D. discoideum two-dimensional, meaning the pillars act as obstacles, as observed in previous studies 38,41 . Cells fully mounting the pillars are rarely observed and excluded from the data.…”
Section: Figure 1dsupporting
confidence: 63%
See 1 more Smart Citation
“…The height and diameter of the pillars is the same (8 µm) and comparable to the typical size of a D. discoideum cell, which varies between 8-15 µm 40 . This ratio between pillar height and cell size is sufficient to keep the motion of starved D. discoideum two-dimensional, meaning the pillars act as obstacles, as observed in previous studies 38,41 . Cells fully mounting the pillars are rarely observed and excluded from the data.…”
Section: Figure 1dsupporting
confidence: 63%
“…These persistent random walks become biased when external guidance cues are present, resulting in an effective drift. Aside from chemical gradients, D. discoideum migration can be influenced topographically 38 . Thus, embedding the amoeba in asymmetric pillar fields, overlaid with a chemical gradient, yields a topo-chemical multi-cue environment capable of studying the significance of topotaxis for highly motile amoeboid movement.…”
Section: Introductionmentioning
confidence: 99%
“…[10] In these arrays, the uniform pillars do not serve as substrates for cell adhesion but as obstacles for the migrating cells, which can be different types of eukaryotic or bacterial cells. [10][11][12][13][14][15] These studies showed that the distance between the pillars affects the migration patterns of cells.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, additional contact sites were provided in the form of pillars to study their effect on the migratory and adhesive behaviour of Dictyostelium discoideum (Arcizet et al, ). Other investigated motile cells include free‐swimming diatoms and dinoflagellates as well as the parasitic protozoans Giardia and Entamoeba (Figure e).…”
Section: Micropillar Arrays For Other Cells and Pathogensmentioning
confidence: 99%
“…iour of Dictyostelium discoideum(Arcizet et al, 2012). Other investigated motile cells include free-swimming diatoms and dinoflagellates as well as the parasitic protozoans Giardia and Entamoeba(Figure 4e).…”
mentioning
confidence: 99%